Crosslinking agent, composition, base material, sealing adhesive film, and electronic component

JP7640753B2Active Publication Date: 2025-03-05HANGZHOU FIRST APPLIED MATERIAL CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023576016
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-26
Filing Date
2021-11-05
Publication Date
2025-03-05
Estimated Expiration
2041-11-05

AI Technical Summary

Benefits of technology

について説明する。 以下、実施例及び比較例に係る架橋剤の製造方法は、架橋剤Aの合成ステップを参照することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640753000001
    Figure 0007640753000001
  • Figure 0007640753000002
    Figure 0007640753000002
  • Figure 0007640753000003
    Figure 0007640753000003
Patent Text Reader

Abstract

The present invention provides a crosslinking agent, a composition, a base material, an adhesive film for sealing, and an electronic component. The crosslinking agent is R 1 x R 2 y [CH3SiO] n n is an even number and 4≦n≦10; R 1 and R 2 are all connected to a Si atom, and R 1 is a group with a terminal double bond, and R 2 is a linear or branched alkyl group having 4 to 14 carbon atoms, x is an even number greater than 1 and less than n, and x+y is equal to n; R 1 There are two of each in para position, R 2 The pair of R exists in para-position, and the pair of R exists in para-position. 1 are the same, and two are para-positioned R 2 are the same and are not in a para-relationship. 1 are the same or different, and are not in a para-position relationship. 2 The crosslinking agent can reduce the probability of migration in the polyolefin resin, thereby improving the creep resistance of the polyolefin resin, and therefore extending the life of the electronic components.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the technical field of optoelectronics, and more particularly to a crosslinking agent, a composition, a base material, an adhesive film for sealing, and an electronic component. [Background technology]

[0002] Polyolefin materials such as ethylene-octene copolymers catalytically synthesized by metallocene catalysts have good insulation, water repellency, PID resistance, and no acidic corrosion, and are therefore widely used as encapsulating materials for highly efficient electronic components such as double-sided PERC cell assemblies, N-type cell assemblies, and double-glass assemblies. Specifically, the encapsulating material can mount, fix, seal, and protect the chip, thereby isolating the chip from the outside and preventing the performance degradation of electrical equipment caused by chip corrosion due to impurities in the air. However, since the traditional encapsulating materials have low heat resistance and tensile resistance, electronic components are easily lost due to energy such as heat, light, and irradiation during encapsulation. As the operation time of electronic components increases, the heat and deformation caused by the long-term operation of electronic components causes further deformation and deterioration of the encapsulating material, which ultimately shortens the life of the electronic components. Summary of the Invention [Problem to be solved by the invention]

[0003] The main object of the present invention is to provide a crosslinking agent, a composition, a base material, an adhesive film for sealing, and an electronic component in order to solve the problem of the short lifespan of electronic components caused by the low heat resistance and tensile resistance of sealing materials in the prior art. [Means for solving the problem]

[0004] In order to achieve the above object, according to one aspect of the present invention, there is provided a crosslinking agent having a cyclic structure of the following general structural formula: R 1 x R 2 y [CH3SiO] n (where n is an even number and 4≦n≦10; R 1 and R 2 are all connected to a Si atom, and R 1 is a group having a terminal double bond, R 2 is a linear or branched alkyl group having 4 to 14 carbon atoms; x is an even number greater than 1 and less than n, and x+y is equal to n; R 1 There are two of each in para position, R 2 The pair of R exists in para-position, and the pair of R exists in para-position. 1 are the same, and two are para-positioned R 2 are the same and are not in a para-relationship. 1 are the same or different, and are not in a para-position relationship. 2 are the same or different.) Furthermore, the above R 1 is C2-C with terminal double bonds 10 is a group of R 2 is C4~C 14 Straight chain alkyl or C4-C 14 is a branched alkyl group.

[0005] Furthermore, the above n is an even number, and 4≦n≦8. Furthermore, the above R 1 is any one selected from vinyl, methacryloxypropyl, and allyl. Furthermore, the above R 2 is C8~C 14 Straight chain alkyl or C8-C 14 R is a branched alkyl 2 is any one selected from octyl, nonyl, decyl, isooctyl, isononyl, and isodecyl.

[0006] According to another aspect of the present invention, there is provided a composition comprising, by weight, 100 parts by weight of a non-polar polyolefin resin and 0.1 to 3 parts by weight of a crosslinking agent, wherein the crosslinking agent is the above-mentioned crosslinking agent. Furthermore, the non-polar polyolefin resin is any one or more selected from low-density polyethylene and ethylene-α-olefin copolymer, and the ethylene-α-olefin copolymer is any one or more selected from linear low-density polyethylene, ethylene-propylene copolymer, ethylene-butylene copolymer, ethylene-pentene copolymer, ethylene-hexene copolymer, and ethylene-octene copolymer.

[0007] According to another aspect of the present invention there is provided a matrix comprising a composition, the composition being the composition described above. According to a further aspect of the present invention, there is provided an adhesive film for sealing, which is obtained by mixing each component in a composition and melt-extruding the mixture, wherein the composition is the aforementioned composition. According to a further aspect of the present invention, there is provided an electronic component including any one of a solar cell, a liquid crystal panel, a field emission device, a plasma display device, and a touch screen, wherein at least one surface of the electronic component is in contact with a sealing adhesive film, and the sealing adhesive film is the sealing adhesive film described above.

[0008] Polyolefin resin materials usually need to be chemically crosslinked in the presence of a crosslinking agent to ensure the heat resistance and tensile resistance of the sealing material. When the technical solution of the present invention is applied, the crosslinking agent is a cyclic silane compound similar to a centrosymmetric structure, and since its positive and negative charge centers overlap, it is a non-polar molecular compound, and based on the principle that "like dissolves like", the compatibility of this crosslinking agent with non-polar polyolefin resin is improved. Meanwhile, the long-chain carbon substituent R 2 The substituent increases the physical entanglement with the molecular chain of the polyolefin resin, further improving the compatibility with the polyolefin resin. Therefore, the above two factors have significantly reduced the migration problem of the crosslinker. In addition, the R 1By using the terminal double bond provided by the substituent as a chemical crosslinking point, it can be chemically bonded to the polyolefin resin molecular chain by the inducing action of heat, light, irradiation, etc., and a more extensive crosslinked structure can be formed, which further improves the creep resistance of the polyolefin resin and further extends the life of electronic components. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] In addition, the embodiments and features of the embodiments in the present application may be combined with each other without causing any contradiction. The present invention will be described in detail below with reference to the embodiments. As analyzed in the background art, in the prior art, there exists a problem of shortening the life span of electronic components due to the low heat resistance and tensile resistance of the encapsulating material. In order to solve this problem, the present invention provides a crosslinking agent, a composition, a base material, an adhesive film for encapsulation, and an electronic component.

[0010] In an exemplary embodiment of the present application, a crosslinker is provided having a cyclic structure of the following general structural formula: R 1 x R 2 y [CH3SiO] n (where n is an even number, and 4≦n≦10; R 1 and R 2 are all connected to Si atoms, and R 1 is a group having a terminal double bond, and R 2 is a linear or branched alkyl group having 4 to 14 carbon atoms, x is an even number greater than 1 and less than n, and x+y is equal to n; R 1 There are two of each in para position, R 2 There are two of each in the para-position.)

[0011] In order to ensure the heat resistance and tensile resistance of the sealing material, polyolefin resin materials usually need to be chemically crosslinked in the presence of a crosslinking agent. The crosslinking agent of the present invention is a cyclic silane compound similar to a centrosymmetric structure, and since its positive and negative charge centers overlap, it is a non-polar molecular compound, and based on the principle that "like dissolves like," the compatibility of this crosslinking agent with non-polar polyolefin resins is improved. On the other hand, the long-chain carbon substituent R 2 The substituents increase the physical entanglement with the molecular chains of the polyolefin resin, further improving the compatibility with the polyolefin resin. Therefore, the above two factors have made it possible to greatly reduce the problem of migration of the crosslinking agent. In addition, the R 1 By using the terminal double bonds provided by the substituents as chemical crosslinking points, they can be chemically bonded to the polyolefin resin molecular chains by the inducing action of heat, light, irradiation, etc., forming a more extensive crosslinked structure, which further improves the creep resistance of the polyolefin resin and extends the life of electronic components.

[0012] In one embodiment of the present application, R 1 is C2-C with terminal double bonds 10 is a group of R 2 is C4~C 14 Straight chain alkyl or C4-C 14 is a branched alkyl group. Preferably, R 1 is C2-C with terminal double bonds 10 It is advantageous for improving the efficiency and effect of polymerization between the crosslinking agent molecule and the polyolefin resin, and is a C4-C 14 Straight chain alkyl or C4-C 14 The branched alkyl group is advantageous in that it improves the degree of physical entanglement with the polyolefin resin molecular chain and further improves the compatibility with the polyolefin resin.

[0013] In one embodiment of the present application, n is an even number, and 4≦n≦8. The larger n is, the larger the cyclic skeleton of the crosslinking agent molecule is, and the deterioration of compatibility in the polyolefin resin due to the large skeleton of the crosslinking agent molecule is reduced as much as possible. Therefore, preferably, n is 4≦n≦8, more preferably, n is 4 or 6, and even more preferably, n is 4. In order to further improve the efficiency of polymerization between the crosslinker molecule and the polyolefin resin molecular chain, it is preferable to add R 1 is any one selected from vinyl, methacryloxypropyl, and allyl.

[0014] Preferably, R 2 is C8~C 14 Straight chain alkyl or C8-C 14 R 2 is any one selected from octyl, nonyl, decyl, isooctyl, isononyl, and isodecyl, which is advantageous in improving the compatibility between the crosslinking agent and the polyolefin resin. In another exemplary embodiment of the present application, there is provided a composition comprising, by weight, 100 parts by weight of a non-polar polyolefin resin and 0.1 to 3 parts by weight of a crosslinking agent, wherein the crosslinking agent is the crosslinking agent described above.

[0015] The crosslinking agent of the present invention is a cyclic silane compound similar to a centrosymmetric structure, and since its positive and negative charge centers overlap, it is a non-polar molecular compound, and based on the principle that "like dissolves like," the compatibility of this crosslinking agent with non-polar polyolefin resins is improved. On the other hand, the long-chain carbon substituent R 2 The substituents increase the physical entanglement with the molecular chains of the polyolefin resin, further improving the compatibility with the polyolefin resin. Therefore, the above two factors have made it possible to greatly reduce the problem of migration of the crosslinking agent. In addition, the R 1By using the terminal double bond provided by the substituent as a chemical crosslinking point, it is possible to chemically bond with the polyolefin resin molecular chain by the inducing action of heat, light, irradiation, etc., and form a more extensive crosslinked structure, thereby improving the creep resistance of the polyolefin resin. Furthermore, by using an encapsulating material obtained from the above composition, the life of electronic components can be extended.

[0016] Of course, those skilled in the art can add additives such as tackifiers, UV stabilizers, UV absorbers, antioxidants, colorants, inorganic fillers, etc. to the above composition according to practical needs, and can also contain compounds capable of generating hydrogen-robbing radicals upon decomposition to the above composition, thereby further enhancing the crosslinking effect between the crosslinker molecules and the polyolefin resin molecules, but we will not go into detail here. In order to further provide a non-polar polyolefin resin having better compatibility with the above-mentioned crosslinking agent, the non-polar polyolefin resin is preferably any one or more selected from low-density polyethylene and ethylene-α-olefin copolymer, and the ethylene-α-olefin copolymer is any one or more selected from linear low-density polyethylene, ethylene-propylene copolymer, ethylene-butylene copolymer, ethylene-pentene copolymer, ethylene-hexene copolymer, and ethylene-octene copolymer.

[0017] In another exemplary embodiment of the present application, a matrix is ​​provided that includes a composition, wherein the composition is the composition described above. The base material obtained using the above composition is more uniform and stable in composition and has a longer service life in addition to superior properties during subsequent use. In a further exemplary embodiment of the present application, there is provided a sealing adhesive film obtained by mixing each component in a composition and melt extruding the mixture, the composition being the aforementioned composition.

[0018] The above-mentioned adhesive film for sealing may be a single-layer adhesive film or a multi-layer adhesive film. When it is a multi-layer adhesive film, at least one layer contains the composition according to the present invention. The sealing adhesive film obtained from the above composition has good sealing effect. In a further exemplary embodiment of the present application, there is provided an electronic component including any one of a solar cell, a liquid crystal panel, a field emission device, a plasma display device, and a touch screen, wherein at least one surface of the electronic component is in contact with a sealing adhesive film, and the sealing adhesive film is the sealing adhesive film described above.

[0019] By using the above-mentioned pressure-sensitive adhesive sealing film to fix, seal and protect electronic components, the influence of external factors on the electronic components can be reduced as much as possible, and therefore the life span of the electronic components can be increased. The beneficial effects of the present invention will now be described with reference to specific examples and comparative examples. Hereinafter, the synthesis steps of crosslinker A can be referred to for the production methods of the crosslinkers according to the examples and comparative examples.

[0020] 0.1 mol of methylvinyldimethoxysilane and 0.1 mol of octylmethyldimethoxysilane were added to a 250 mL round-bottom flask, and then 0.2 mol of hydrochloric acid solution at pH 5 was added. The mixture was stirred in an oil bath at 50°C for 5 hours to react, and a clear solution was obtained. After removing the by-product methanol using a rotary evaporator, 5 g of anhydrous magnesium sulfate was added, dried for 24 hours, and filtered to obtain a clear liquid. Finally, the mixture was separated and purified using a silica gel column bonded with carbon-18. The mobile phase was methanol, and the last fraction that flowed out was crosslinker A. Detection was performed using a GC-MS gas chromatography mass spectrometry device, and the specific parameters are shown in Table 1.

[0021] [Table 1]

[0022] Crosslinker A: In GC-MS, the peak appeared at 18.4 minutes and the molecular weight was 516.29.

[0023] [ka]

[0024] Crosslinker B: Where R3 is octyl. In GC-MS, the peak appeared at 21.5 minutes and the molecular weight was 688.33.

[0025] [ka]

[0026] Crosslinker C: Where R4 is octyl and R5 is decyl. GC-MS showed a peak appearance time of 24.7 minutes with a molecular weight of 1088.65.

[0027] [ka]

[0028] Crosslinker D: Wherein R6, R8 are octyl, and R7 is decyl. In GC-MS, the peak appeared at 29.2 minutes and the molecular weight was 1418.89.

[0029] [ka] Crosslinker E:

[0030] [ka]

[0031] Crosslinker: TAIC Example 1 Ethylene-octene copolymer (DOW Engage PV8669) 100 parts by weight, crosslinker A 1 part by weight (R1 2R 2 2[CH3SiO]4 (where R 1 is vinyl, R 2 is octyl.)) was prepared, and the two substances were mixed in a planetary mixer until the crosslinker was completely absorbed into the ethylene-octene copolymer particles and the surface of the particles was dry. The dried particles were plasticized and extruded in a single screw extruder with an aspect ratio of 32:1, a screw diameter of 150 mm, and a bushing temperature of 60-90°C. Then, a film was formed and cast using a T-die, and pressed with an embossing roller and a rubber roller to form a specific pattern on the surface, after which it was cooled to room temperature with a cooling roller and wound up to obtain a 0.6 mm thick adhesive film for sealing.

[0032] Example 2 In Example 2, compared with Example 1, R 1 is methacryloxypropyl, and the difference is that a sealing adhesive film having a thickness of 0.6 mm is finally obtained. Example 3 In Example 3, compared with Example 1, R 1 is allyl, and the difference is that a sealing adhesive film having a thickness of 0.6 mm is finally obtained.

[0033] Example 4 In Example 4, compared with Example 1, R 2 The difference is that the final adhesive film for sealing has a thickness of 0.6 mm. Example 5 In Example 5, compared with Example 1, R 2 The difference is that the resin is butyl, and a sealing adhesive film having a thickness of 0.6 mm is finally obtained.

[0034] Example 6 In Example 6, compared with Example 1, The difference is that the amount of crosslinking agent A is 3 parts by weight, and a sealing adhesive film having a thickness of 0.6 mm is finally obtained. Example 7 In Example 7, compared with Example 1, The difference is that the amount of crosslinking agent A is 0.1 parts by weight, and a sealing adhesive film having a thickness of 0.6 mm is finally obtained.

[0035] Example 8 In Example 8, compared with Example 1, The difference is that low-density polyethylene is used instead of ethylene-octene copolymer, resulting in a 0.6 mm thick adhesive sealing film. Example 9 In Example 9, compared with Example 1, The difference is that ethylene-butylene copolymer is used instead of ethylene-octene copolymer, and the final adhesive film for sealing is 0.6 mm thick.

[0036] Example 10 In Example 10, compared with Example 1, The difference is that the crosslinking agent is crosslinking agent B, and a sealing adhesive film having a thickness of 0.6 mm is finally obtained. Example 11 In Example 11, compared with Example 1, The difference is that the crosslinking agent is crosslinking agent C, and a sealing adhesive film having a thickness of 0.6 mm is finally obtained.

[0037] Example 12 In Example 12, compared with Example 1, The difference is that the crosslinking agent is crosslinking agent D, and a sealing adhesive film having a thickness of 0.6 mm is finally obtained.

[0038] Example 13 Ethylene-octene copolymer (DOW Engage PV8669) 100 parts by weight, crosslinker A 1 part by weight (R 1 2R 2 2[CH3SiO]4 (where R 1 is vinyl, R 2is octyl.)) and 0.5 parts by weight of tert-butylperoxy 2-ethylhexyl carbonate (TBEC) were prepared, and these three substances were mixed in a planetary mixer until the crosslinking agent was completely absorbed into the ethylene-octene copolymer particles and the surface of the particles was dry. The dried particles were plasticized and extruded in a single-screw extruder with an aspect ratio of 32, a screw diameter of 150 mm, and a bushing temperature of 60-90°C. Then, a film was formed and cast using a T-die, pressed with an embossing roller and a rubber roller to form a specific pattern on the surface, and then cooled to room temperature with a cooling roller and wound up to obtain a 0.6 mm thick adhesive film for sealing.

[0039] Example 14 Ethylene-octene copolymer (DOW Engage PV8669) 100 parts by weight, crosslinker A 1 part by weight (R 1 2R 2 2[CH3SiO]4 (where R 1 is vinyl, R 2 is octyl.) and 0.5 parts by weight of benzophenone were prepared, and these three substances were mixed in a planetary mixer until the crosslinking agent was completely absorbed into the ethylene-octene copolymer particles and the surface of the particles was dry. The dried particles were plasticized and extruded in a single-screw extruder with an aspect ratio of 32, a screw diameter of 150 mm, and a bushing temperature of 60-90°C. Then, a film was formed and cast using a T-die, and pressed with an embossing roller and a rubber roller to form a specific pattern on the surface, and then cooled to room temperature with a cooling roller and wound up to obtain a 0.6 mm thick adhesive film for sealing.

[0040] Comparative Example 1 In Comparative Example 1, compared with Example 1, The difference is that the amount of crosslinking agent A is 0.01 parts by weight, and a sealing adhesive film having a thickness of 0.6 mm is finally obtained. Comparative Example 2 In Comparative Example 2, compared with Example 1, The difference is that the amount of crosslinking agent A is 4 parts by weight, and a sealing adhesive film having a thickness of 0.6 mm is finally obtained.

[0041] Comparative Example 3 In Comparative Example 3, compared with Example 1, The difference is that the crosslinking agent is TAIC, and a 0.6 mm thick adhesive film for sealing is finally obtained. Comparative Example 4 In Comparative Example 4, compared with Example 1, The difference is that the crosslinking agent is crosslinking agent E, and a sealing adhesive film having a thickness of 0.6 mm is finally obtained.

[0042] (1) Cross-linking degree and tensile strength test The adhesive films for sealing obtained in Examples 1 to 12 and Comparative Examples 1 to 4 were irradiated with a high-energy electron beam, respectively, with a radiation dose of 40 KGy. The adhesive film of Example 13 was laminated with a laminator at 150°C for 18 minutes. The adhesive film for sealing of Example 14 was irradiated with an ultraviolet lamp with a central wavelength of 365 nm, with a radiation dose of 5000 mJ / cm. 2 The adhesive film for sealing after electron beam irradiation, the adhesive film for sealing laminated at high temperature, or the adhesive film for sealing after ultraviolet irradiation was weighed in an amount of 1 g, and subjected to Soxhlet extraction using boiling xylene for 5 hours. The film was then filtered through a 30-mesh stainless steel filter, placed in a vacuum oven at 145°C and dried under reduced pressure for 3 hours, and finally the weight of the material remaining on the net was calculated as A (g). The degree of crosslinking was calculated by the formula: degree of crosslinking (weight%) = A x 100%. The surface pattern of the radiated adhesive sealing film was removed using a laminator, and then the film was punched into a standard dumbbell-shaped test strip with a thickness of 0.6 mm using a standard die, and the tensile strength (unit: MPa) of the resulting adhesive sealing film was tested according to the ASTM D638-8 standard.

[0043] (2) Absorption capacity of auxiliary agents 50 mL of 70% by weight methanol solution was prepared using crosslinkers A-E and TAIC, respectively, for use. 1 g of ethylene-octene copolymer pellets (DOW EngagePV 8669) was weighed and placed in a stainless steel cage, and then the stainless steel cage was immersed in the methanol solution, allowing the particles to be completely submerged in the solution. The immersion was continued for 4 hours while maintaining the environmental temperature at 25°C. After the immersion was completed, the polymer particles were taken out, the liquid on the surface was wiped off with a paper towel, and weighed to obtain the value B (g), and the absorption capacity of the auxiliary = (B-1) x 100%. Table 2 shows the tensile strength of the sealing adhesive films obtained in the above Examples 1 to 14 and Comparative Examples 1 to 4.

[0044] [Table 2] Table 3 shows the absorption capacity of the crosslinking agents A to E and the TAIC auxiliary.

[0045] [Table 3]

[0046] From the data in Table 3 above, it can be seen that the compatibility of the crosslinking agent of the present invention with polyolefin resins is obviously better than that of the crosslinking agent E and TAIC of the prior art with polyolefin resins. From the above description, it can be seen that the above-described embodiments of the present invention achieve the following technical effects.

[0047] In order to ensure the heat resistance and tensile resistance of the sealing material, polyolefin resin materials usually need to be chemically crosslinked in the presence of a crosslinking agent. The crosslinking agent of the present invention is a cyclic silane compound similar to a centrosymmetric structure, and since its positive and negative charge centers overlap, it is a non-polar molecular compound, and based on the principle that "like dissolves like," the compatibility of this crosslinking agent with non-polar polyolefin resins is improved. On the other hand, the long-chain carbon substituent R 2The substituents increase the physical entanglement with the molecular chains of the polyolefin resin, further improving compatibility with the polyolefin resin. Therefore, the above two factors have made it possible to greatly reduce the problem of migration of the crosslinking agent. In addition, the R 1 By using the terminal double bond provided by the substituent as a chemical crosslinking point, it can be chemically bonded to the polyolefin resin molecular chain by the inducing action of heat, light, irradiation, etc., and a more extensive crosslinked structure can be formed, which further improves the creep resistance of the polyolefin resin and further extends the life of electronic components.

[0048] The above is only a preferred embodiment of the present invention, and is not intended to limit the present invention. Those skilled in the art can make various modifications and variations to the present invention. Any amendments, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention should be included within the patent scope of the present invention.

Claims

1. A crosslinking agent having a cyclic structure of the following general structural formula: R 1 x R 2 y [CH 3 SiO] n (where n is an even number and 4≦n≦10; R 1 and R 2 are all connected to a Si atom, and the R 1 is a group having a terminal double bond, The R 2 is a linear or branched alkyl group having 4 to 14 carbon atoms; x is an even number greater than 1 and less than n, and x+y is equal to n; The R 1 Two of each of the R 2 The R 1 are the same, and the R 2 are the same, and the R 1 are the same or different, and are not in a para-position relationship. 2 are the same or different, and the para positions refer to a situation where two R 1 s that satisfy the requirement that two R 1 s are present at para positions along the clockwise or counterclockwise direction of the cyclic structure of the crosslinking agent have the same number of Si atoms and the same number of O atoms, and a situation where two R 2 s that satisfy the requirement that two R 2 s that are present at para positions have the same number of Si atoms and the same number of O atoms.)

2. The R 1 is a C with a terminal double bond 2 ~C 10 wherein R 2 is C 4 ~C 14 Linear alkyl or C 4 ~C 14 2. The crosslinking agent according to claim 1, wherein the branched alkyl group is

3. 2. The crosslinking agent according to claim 1, wherein n is an even number and 4≦n≦8.

4. The R 1 The crosslinking agent according to claim 1, wherein is any one selected from the group consisting of vinyl, methacryloxypropyl, and allyl.

5. The R 2 is C 8 ~C 14 Linear alkyl or C 8 ~C 14 is a branched alkyl of the formula R 2 The crosslinking agent according to any one of claims 1 to 4, wherein is any one selected from octyl, nonyl, decyl, isooctyl, isononyl, and isodecyl.

6. A composition comprising, by weight, 100 parts by weight of a non-polar polyolefin resin and 0.1 to 3 parts by weight of a crosslinking agent, A composition, characterized in that the crosslinking agent is the crosslinking agent according to any one of claims 1 to 5.

7. The composition according to claim 6, wherein the non-polar polyolefin resin is any one or more selected from low-density polyethylene and ethylene-α-olefin copolymer, and the ethylene-α-olefin copolymer is any one or more selected from linear low-density polyethylene, ethylene-propylene copolymer, ethylene-butylene copolymer, ethylene-pentene copolymer, ethylene-hexene copolymer, and ethylene-octene copolymer.

8. A matrix comprising a composition, The composition is a composition according to claim 6 or 7.

9. A sealing adhesive film obtained by mixing each component in a composition and melt-extruding the mixture, 8. A sealing adhesive film, comprising the composition according to claim 6 or 7.

10. An electronic component including any one of a solar cell, a liquid crystal panel, a field emission device, a plasma display device, and a touch screen, An electronic component, characterized in that at least one surface of the electronic component is in contact with an adhesive sealing film, the adhesive sealing film being the adhesive sealing film according to claim 9.

Citation Information

Patent Citations

  • JP1973088199A

  • 2,4,6,8-tetramethyl-4,6,8-trivinyl-2-(3-methacryloxypropyl) cyclotetrasiloxane

    JP1988014787A

  • Silicone-based composition containing silicone-based polymer particle, and method for producing the same

    JP2009263401A

  • Curable resin composition, and cured product, sealing agent, and optical semiconductor device using same

    WO2013176238A1